2021
DOI: 10.1371/journal.pntd.0009391
|View full text |Cite
|
Sign up to set email alerts
|

Impact of deltamethrin-resistance in Aedes albopictus on its fitness cost and vector competence

Abstract: Background Aedes albopictus is one of the most invasive species in the world as well as the important vector for mosquito-borne diseases such as dengue fever, chikungunya fever and zika virus disease. Chemical control of mosquitoes is an effective method to control mosquito-borne diseases, however, the wide and improper application of insecticides for vector control has led to serious resistance problems. At present, there have been many reports on the resistance to pyrethroid insecticides in vector mosquitoes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 31 publications
2
27
0
Order By: Relevance
“…As a mosquito-borne infectious disease with the fastest transmission speed in the world, dengue fever has become 1 of the diseases threatening global public health. [ 19 ] The influence of climate change and travel to/from endemic countries are important factors leading to the disease outbreak. [ 20 ] An analysis of imported cases from 2014 to 2018 in China showed that the dengue patients were mainly aged between 21 and 50 years old made up the most farmers and unemployed people.…”
Section: Discussionmentioning
confidence: 99%
“…As a mosquito-borne infectious disease with the fastest transmission speed in the world, dengue fever has become 1 of the diseases threatening global public health. [ 19 ] The influence of climate change and travel to/from endemic countries are important factors leading to the disease outbreak. [ 20 ] An analysis of imported cases from 2014 to 2018 in China showed that the dengue patients were mainly aged between 21 and 50 years old made up the most farmers and unemployed people.…”
Section: Discussionmentioning
confidence: 99%
“…In deltamethrin-resistant Aedes albopictus there was a fitness cost but a decrease in its competence as a vector. However, the resistant strain still could complete the period of incubation (Deng et al, 2021).…”
Section: Oxidative Stress Through Infectionmentioning
confidence: 98%
“…More recently, two researches focused on influence of vector competence of pyrethroid resistant Ae. aegypti for Zika virus, the results were similar between the resistant group and susceptible group (Dos Santos et al ., 2020; Parker-Crockett et al ., 2021), however a reduced vector competence was found in resistant Aedes albopictus for dengue virus (serotype 2) (Deng et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%